Simulation Manikin Modifications for High-Fidelity Training of Advanced Airway Procedures. Issue 9 (1st May 2016) - Hirsch, Jan; Generoso, Jose R.; Latoures, Renee; Acar, Yahya; Fidler, Richard L.
Abstract : Thoracic anesthesia procedures are challenging to master during anesthesia training. A Laerdal ALS Simulator® manikin was modified by adding a bronchial tree module to create fidelity to the fourth generation. After modification, placement of endotracheal tubes up to 8.0 mm is possible by direct laryngoscopy, video laryngoscopy, and fiberoptically; in addition, it allows fiberoptically guided insertion of endobronchial blockers. Insertion of left and right 35-Fr double-lumen tubes permits double- and single-lung ventilation with continuous positive airway pressure and positive end-expiratory pressure. This anatomical modification created a high-fidelity training tool for thoracic anesthesia that has been incorporated into educational curricula for anesthesia.